Influence of Iron on Bone Homeostasis - Enikő Balogh; György Paragh; Viktória Jeney (MDPI AG, 2018)
Bone homeostasis is a complex process, wherein osteoclasts resorb bone and osteoblasts produce new bone tissue. For the maintenance of skeletal integrity, this sequence has to be tightly regulated and orchestrated. Iron overload as well as iron deficiency disrupt the delicate balance between bone destruction and production, via influencing osteoclast and osteoblast differentiation as well as activity. Iron overload as well as iron deficiency are accompanied by weakened bones, suggesting that balanced bone homeostasis requires optimal—not too low, not too high—iron levels. The goal of this review is to summarize our current knowledge about how imbalanced iron influence skeletal health. Better understanding of this complex process may help the development of novel therapeutic approaches to deal with the pathologic effects of altered iron levels on bone.